2018
DOI: 10.5194/hess-2018-471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring Groundwater Storage Depletion Using Gravity Recovery and Climate Experiment (GRACE) Data in the Semi-Arid Catchments

Abstract: Abstract. The Bakhtegan catchment, an important agricultural region in south-western Iran, has suffered groundwater depletion in recent years. As groundwater is considered the main source of fresh water in the catchment, especially for agriculture, monitoring groundwater responses to irrigation is important. Gravity Recovery and Climate Experiment (GRACE) satellite data can help determine water mass changes in catchments and assess water volume changes, but have been under-used to date in water resources manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…It is then essential to explore indirect and reliable methods for understanding the impact of rainfall and pumping on groundwater storage changes. GRACE has been demonstrated to be useful to develop insights into how groundwater storage varies [9,39,65,71,72]. In the present study, GRACE allowed more or less correct assessments of the dynamics of TWS in the TMB, a semi-arid area with scarce data.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…It is then essential to explore indirect and reliable methods for understanding the impact of rainfall and pumping on groundwater storage changes. GRACE has been demonstrated to be useful to develop insights into how groundwater storage varies [9,39,65,71,72]. In the present study, GRACE allowed more or less correct assessments of the dynamics of TWS in the TMB, a semi-arid area with scarce data.…”
Section: Discussionmentioning
confidence: 86%
“…Without ground data covering the TMB, it is impossible to make a comparison between GRACE data and ground measurements, which does not correspond to any of the objectives of this study. This issue has been widely discussed in the literature, and the majority of the authors find a good match between GRACE and in-situ measurements [9,31,[50][51][52].…”
Section: Groundwater-monitoring Wells In the Arlit Mining Areamentioning
confidence: 88%
See 2 more Smart Citations
“…A recent study in Saudi Arabia found an annual decreasing trend of 1 cm per year in the groundwater thickness using GRACE data [42]. Similarly, a groundwater thickness reduction of 0.76 cm per year was found in Bakhtegan catchment of Iran [24]. Groundwater is mainly used for agriculture purposes, as the majority of the domestic and industrial water demand is fulfilled by desalination.…”
Section: Groundwater Assessmentmentioning
confidence: 96%